2009
DOI: 10.1161/circgenetics.109.853374
|View full text |Cite
|
Sign up to set email alerts
|

SCN5A Mutations and the Role of Genetic Background in the Pathophysiology of Brugada Syndrome

Abstract: Background-Mutations in SCN5A are identified in Ϸ20% to 30% of probands affected by Brugada syndrome (BrS).However, in familial studies, the relationship between SCN5A mutations and BrS remains poorly understood. The aim of this study was to investigate the association of SCN5A mutations and BrS in a group of large genotyped families. Methods and Results-Families were included if at least 5 family members were carriers of the SCN5A mutation, which was identified in the proband. Thirteen large families composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
182
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(196 citation statements)
references
References 39 publications
10
182
1
3
Order By: Relevance
“…Indeed, the classical concept of BrS as a mendelian disease has been recently modified according to the idea of arrhythmia genomics, suggesting that different variants may contribute to the phenotype and sodium channel defects may be one of the contributory causes and not necessarily the main. 7,41 Inter-individual genetic differences may modulate excitation-contraction physiology, influencing arrhythmia susceptibility and may even explain differences in clinical phenotype presentation among distinct ethnicities. 42,43 Ion channels carry out their function as part of multiproteic complexes, interacting with accessory subunits and regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the classical concept of BrS as a mendelian disease has been recently modified according to the idea of arrhythmia genomics, suggesting that different variants may contribute to the phenotype and sodium channel defects may be one of the contributory causes and not necessarily the main. 7,41 Inter-individual genetic differences may modulate excitation-contraction physiology, influencing arrhythmia susceptibility and may even explain differences in clinical phenotype presentation among distinct ethnicities. 42,43 Ion channels carry out their function as part of multiproteic complexes, interacting with accessory subunits and regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recently it has been reported that SCN5A mutation are not directly causal for BrS phenotype. 37 We need to consider other genetic effects because the balance of all currents active during the early phases of the AP recapitulate the BrS phenotype. Each genetic background of the patient can lead different phenotype by amitriptyline.…”
Section: Discussionmentioning
confidence: 99%
“…67 In addition, there are large SCN5A positive families that have affected individuals who are noncarriers, suggesting a modifier role rather than direct causation in these pedigrees. 86 Many other genes have been associated with the syndrome (Table I). One study identified mutations of the L-type calcium channel (encoded by CACNA1C, CACNB2B, and CACNA2D1) in 10%-15% of BrS cases.…”
Section: Causes Of Sads and The Role Of Genetic Testingmentioning
confidence: 99%